Urinary micro-RNA expressions and protein concentrations may differentiate bladder cancer patients from healthy controls - ILGIN, CAN; FİLİNTE, DENİZ; GÜLLÜ AMURAN, GÖKÇE; AKKİPRİK, MUSTAFA (SPRINGER, 2020)
Purpose To determine expression differences of urine exosomal miR-19b1-5p, 21-5p, 136-3p, 139-5p, 210-3p and concentration differences of urinary BLCA-4, NMP22, APE1/Ref1, CRK, VIM between bladder cancer, follow-up patients, and control samples, to evaluate diagnostic importance of these differences and establish a diagnostic panel for bladder cancer. Methods Urine samples of 59 bladder cancer patients, 34 healthy controls, and 12 follow-up patients without recurrence were enrolled to this study. Real-time PCR and ELISA were performed to determine urine exosomal miR-19b1-5p, 21-5p, 136-3p, 139-5p, 210-3p expressions and urinary BLCA-4, NMP22, APE1/Ref1, CRK, VIM, creatinine concentrations. Logistic regression analyses were performed to determine the diagnostic panel, the sensitivity, and specificity of the panel assessed by the ROC curve analysis. p values < 0.05 were considered statistically significant. Results In bladder cancer risk groups, mir-139, -136, -19 and 210 expressions or positivity were found to be different and concentrations of urinary Ape1/Ref1, BLCA4, CRK, and VIM increased by twofold on average compared to healthy controls. Logistic regression and ROC analyses revealed that panel could differentiate bladder cancer patients from healthy controls with 80% sensitivity and 88% specificity (AUC = 0.899), low-risk patients from controls with 93% sensitivity and 95.5% specificity (AUC = 0.976). Despite the low number of samples, our findings suggest that urine exosomal miR-19b1-5p, 136-3p, 139-5p expression, and urinary APE1/Ref1, BLCA-4, CRK concentrations are promising candidates in terms of bladder cancer diagnosis. Conclusions Although our panel has great sensitivity for early detection of BC, it needs to be validated in larger populations.
Keywords: Bladder cancer; Urinary protein; Urine exosomal miRNA; Urinary biomarker; Bladder cancer diagnosis; BIOMARKERS; NORMALIZATION; DIAGNOSIS; SURVEILLANCE